Common variations in the ALMS1 gene do not contribute to susceptibility to type 2 diabetes in a large white UK population. - Patel, S; Minton, J; Weedon, M; Frayling, T; Ricketts, C; Hitman, G; McCarthy, M; Hattersley, A; Walker, M; Barrett, T (2006)
AIMS/HYPOTHESIS: Alström syndrome is a rare monogenic disorder characterised by retinal dystrophy, deafness and obesity. Patients also have insulin resistance, central obesity and dyslipidaemia, thus showing similarities with type 2 diabetes. Rare mutations in the ALMS1 gene cause severe gene disruption in Alström patients; however, ALMS1 gene polymorphisms are common in the general population. The aim of our study was to determine whether common variants in ALMS1 contribute to susceptibility to type 2 diabetes in the UK population. METHODS: Direct sequencing was performed on coding regions and intron/exon boundaries of the ALMS1 gene in 30 unrelated probands with type 2 diabetes. The linkage disequilibrium (LD; D' and r2) and haplotype structure were examined for the identified variants. The common (minor allele frequency [MAF] >5%) single-nucleotide polymorphisms tagging the common haplotypes (tagged SNPs [tSNPs]) were identified and genotyped in 1985 subjects with type 2 diabetes, 2,047 control subjects and 521 families. RESULTS: We identified 18 variants with MAF between 6 and 38%. Three SNPs efficiently tagged three common haplotypes (rs1881245, rs3820700 and rs1320374). There was no association (all p > 0.05) between the tSNPs and type 2 diabetes in the case-control study and minor alleles of the tSNPs were not overtransmitted to probands with type 2 diabetes in the family study. CONCLUSIONS/INTERPRETATION: Common variations in the ALMS1 gene were not associated with type 2 diabetes in a large study of a white UK population.